Optimal sizing and economic assessment of diesel and solar mills for cereal milling in rural areas of Senegal - Diop, Moustapha; Ndiaye, Mouhamadou Falilou; Gueye, Ibrahima; Kebe, Abdoulaye; Dia, Omar (Institute of Advanced Engineering and Science, 2024)
This paper aims at using life cycle costing (LCC) to assess the economic viability of solar and diesel mills for cereal milling, adopting several scenarios of village sizes in Senegal and time perspectives. This work is intended to provide decision-makers and stakeholders with valuable information for selecting optimal milling systems, taking into account both economic and village size considerations. The methodology adopted is based on system specifications and daily cereal consumption profiles. To determine the economic performance of systems, three types of villages are evaluated and analyzed in detail from short, medium, and long-term perspectives. The results indicate that solar mills are the most economical systems for milling cereals in remote villages in the long term, with a potential economic gain of 10%, 31%, and 41% for small, medium, and big villages respectively, compared to diesel mills. However, solar mills are less promising in the short term.